INTEGRATIVE MOTIVATION OF JUNIOR HIGH SCHOOL IN LEARNING ENGLISH IN A GLOBALIZING WORLD - Adhiarto, Ogik (Jurnal Penelitian Humaniora, 2013)
This research article deals with motivation of children aged 11-12 years old, as they begin formal study of English in an urban junior high school. The research used closed and open questionnaire items, backed up by class observations and interviews with a selected group of learners. The results indicates that very high levels of motivation to learn the language were found throughout the cohort, including both integrative and instrumental orientations, but these two traditionally distinct constructs were found to be almost indistinguishable. It is argued that as English loses its association with par- ticular Anglophone cultures and is instead identified with the powerful forces of globalization, the desire to ?integrate? loses its explanatory power in many EFL contexts. Individuals may aspire towards a ?bicultural? identity which incorporates an English- speaking globally-involved version of themselves in addition to their local L1-speaking self. It is speculated that changes in individuals? motivation to learn the language may therefore be partly explained by reference to ongoing processes of identification, especially during the formative years of adolescence.